EFFECT OF ADDITIONAL GINGER (Zingiber officinale var. amarum) ON FEED ON THE GROWTH AND SURVIVAL LEVEL OF GOLDFISH (Cyprinus Carpio) - Nining Syafirah; Muhammad Marzuki; Baiq Hilda Astriana (Aquaculture Department, University of Mataram, 2021)
Goldfish is one of the most popular freshwater cultivated fish because it is one of the freshwater commodities that has economic value and is sold at a price that is affordable to all groups. Ginger is a natural ingredient that can stimulate fish growth. The purpose of this study was to determine the effect of adding ginger to feed and to determine a good dose of ginger for growth and survival rates of carp (Cyprinus carpio). This research was conducted by experimental method using completely randomized design (CRD) with 5 treatments and 3 replications. The treatments given were Treatment 1: 0 grams, without adding ginger / kg of feed (control), Treatment 2: 2.5 grams of ginger / kg of feed, Treatment 3: 5 grams of ginger rhizome / kg of feed, Treatment 4: 7.5 grams of ginger / kg of feed, Treatment 5: 10 grams of ginger / kg of feed. The results showed that the addition of ginger had no significant effect on absolute length growth, absolute weight growth, feed conversion ratio, and feed efficiency, but had a significant effect on the survival rate of goldfish (cyprinus corpio). And a good dose of ginger is in P2 treatment with a dose of 2.5 grams of ginger, because it has been able to show a good survival rate of 100%.